Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1177/1358863x15584753
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid exposure and receptor activity modulate microvascular endothelial function in African Americans with and without hypertension

Abstract: Background Prior work suggests blood pressure in African Americans (AAs) is more sensitive to the effects of aldosterone than in Caucasians. This mechanism may relate to a negative response of the vascular endothelium to aldosterone, including reduced glucose-6-phosphate dehydrogenase (G6PD) activity. Methods Thirty-three African Americans (eleven hypertensives, twenty-two controls) without evidence of diabetes or metabolic syndrome completed protocol. The protocol included measurement of in vivo microvascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, aldosterone impairs endothelial function in normal resistance vessels, whilst aldosterone can reverse hypertension-related endothelial dysfunction in arterioles 148 . Similar benefits have been observed with eplerenone which reduces vascular stiffness, collagen/elastin ratio, pro-inflammatory mediators and systemic inflammatory markers in patients with hypertension.…”
Section: Mineralocorticoid Receptor Antagonistsmentioning
confidence: 99%
“…Furthermore, aldosterone impairs endothelial function in normal resistance vessels, whilst aldosterone can reverse hypertension-related endothelial dysfunction in arterioles 148 . Similar benefits have been observed with eplerenone which reduces vascular stiffness, collagen/elastin ratio, pro-inflammatory mediators and systemic inflammatory markers in patients with hypertension.…”
Section: Mineralocorticoid Receptor Antagonistsmentioning
confidence: 99%
“…Hypertensive African-Americans had impaired endothelial function, as measured by pulse arterial tonography and by ex vivo studies of adipose vessels, which was improved with spironolactone treatment. Conversely, normotensive subjects had impaired endothelial function after Aldo administration, which was also prevented by spironolactone ( 17 ). Hypertensive subjects had an associated decrease in arteriolar glucose-6-phosphate dehydrogenase (G6PD) activity compared to non-hypertensives.…”
Section: Mr In the Vascular Endothelium Contributes To Endothelial Cementioning
confidence: 99%
“…In contrast to the protective role of MR activation in brachial artery FMD observed in previous studies of healthy populations [18*,36], normotensive African-Americans developed endothelial microvascular dysfunction (evaluated by digital pulse arterial tonometry) in response to acute aldosterone administration and this was prevented by spironolactone[37*]. It was suggested that the endothelial dysfunction in healthy African-Americans may be due to decreased vascular G6PD activity in this population.…”
Section: Introductionmentioning
confidence: 69%